Competitions as a stimulating and evaluation method on algorithms and complexity course (IEEE Global Engineering Education Conference, 2017)
Academic competitions challenge students to work harder, engage more to learn the academic content, can make the material more interesting and get the students excited during the learning process. In this paper we present our experience in the organization of laboratory exercises of the Algorithms and complexity faculty courses in the form of competitions. The specific set of students attending this course, where most of them are the best ones in the field of algorithms and programming in our country, motivated us to design a subject which will be challenging to those students, while at the same time it will take care about the other students.